Enabling high performance n-type metal oxide semiconductors at low temperatures for thin film transistors. Issue 9 (9th April 2020) - Tiwari, Nidhi; Nirmal, Amoolya; Kulkarni, Mohit Rameshchandra; John, Rohit Abraham; Mathews, Nripan
Abstract : The review highlights low temperature activation processes for high performance n-type metal oxide semiconductors for TFTs. Abstract : Amorphous oxide semiconductors have drawn considerable attention as a replacement for ubiquitous silicon based technologies. By virtue of their flexible substrate compatibility and transparency, amorphous metal oxide semiconductor (AOS) thin film transistors (TFTs) are being explored in emerging flexible/transparent technologies. However, rapid advances in such technologies require the development of high-performance thin film transistors, which can be fabricated at low processing temperatures. In this review paper, we discuss the recent progress made in n-type semiconductor TFTs activated at low temperatures both on rigid and flexible substrates with a focus on the replacement of conventional high temperature annealing. Several low temperature processing approaches that have been reported in both vacuum deposited and solution processed n-type metal oxide semiconductor based thin film transistors are evaluated, with an emphasis on some novel techniques which can effectively modulate the electronic properties of the n-type metal oxide semiconductor systems at low temperatures. The final part of this review draws conclusions and discusses the outlook for future research efforts in achieving low temperature activated high performance n-type TFTs.